OVERVIEW OF ANATOMICAL PATHOLOGY LABORATORY WASTE PROCESSING AT YOGYAKARTA CITY HOSPITAL - Winasari, Dea; Nailufar, Yuyun; Putri, Widaninggar Rahma (Jurnal Mitra Kesehatan, 2025)
Anatomical pathology laboratory plays an important role in helping doctors diagnose diseases through the analysis of biological samples, but every process in the anatomical pathology laboratory poses risks to workers, including anatomical pathology medical waste which is hazardous if not managed properly. Objective: This study assesses whether the solid and liquid waste management procedures implemented in the anatomical pathology laboratory of Yogyakarta City Hospital are in accordance with standards. Method: This study is a descriptive observational study. Results: The study shows that the management of pathological and hazardous waste in the anatomical pathology laboratory of Yogyakarta City Hospital is in accordance with PMK No. 2 of 2023 and the implementation of regulations and SOPs effectively minimizes risks and maintains a safe work environment. Conclusion: The management of pathological and hazardous waste in the Anatomical Pathology Laboratory of Yogyakarta City Hospital . meets regulatory standards and SOPs, supported by good staff understanding. Overall, the implemented procedures effectively maintain occupational safety, although there are still some challenges related to limited personnel.